2022
DOI: 10.1096/fj.202200463r
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity analysis of astrocytes following spinal cord injury at single‐cell resolution

Abstract: Astrocytes play many important functions in response to spinal cord injury (SCI) in an activated manner, including clearance of necrotic tissue, formation of protective barrier, maintenance of microenvironment balance, interaction with immune cells, and formation of the glial scar. More and more studies have shown that the astrocytes are heterogeneous, such as inflammatory astrocyte 1 (A1) and neuroprotective astrocyte 2 (A2) types. However, the subtypes of astrocyte resulting from SCI have not been clearly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Our results and other studies ( Li et al, 2016 ; Hockley et al, 2019 ; Renthal et al, 2020 ; Parpaite et al, 2021 ; Wang et al, 2021 ) have shown that neurons in the peripheral ganglion have distinct subpopulations that are consistent with neurons of different functions, but there are fewer relevant studies on SGCs subtypes in the peripheral ganglion. Astrocytes, as glial cells similar to SGCs in the CNS, a series of correlative studies based on scRNA-seq have demonstrated the diversity of astrocytes in different regions of the brain and the variation of astrocyte subtypes in different disease ( Batiuk et al, 2020 ; Hasel et al, 2021 ; Hou et al, 2022 ; Ma et al, 2022 ; Sadick et al, 2022 ). Compared to astrocytes, there are currently fewer studies on single-cell transcription of SGCs subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and other studies ( Li et al, 2016 ; Hockley et al, 2019 ; Renthal et al, 2020 ; Parpaite et al, 2021 ; Wang et al, 2021 ) have shown that neurons in the peripheral ganglion have distinct subpopulations that are consistent with neurons of different functions, but there are fewer relevant studies on SGCs subtypes in the peripheral ganglion. Astrocytes, as glial cells similar to SGCs in the CNS, a series of correlative studies based on scRNA-seq have demonstrated the diversity of astrocytes in different regions of the brain and the variation of astrocyte subtypes in different disease ( Batiuk et al, 2020 ; Hasel et al, 2021 ; Hou et al, 2022 ; Ma et al, 2022 ; Sadick et al, 2022 ). Compared to astrocytes, there are currently fewer studies on single-cell transcription of SGCs subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell transcriptomics. More recent transcriptome work in the SCI field has included studies utilizing single cell RNA-Seq (scRNA-Seq) [98,[110][111][112][113][114][115][116], including a recent atlas of spinal cord injury in mice [114]. Due to the complexities of scRNA-Seq data, including cell typing and the disparity between limited sample numbers and large numbers of cells per sample, as well as a different modality for viewing scRNA-Seq data, we chose not to include that data at this time to focus on the more broadly available bulk RNA-Seq datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk RNA-seq datasets (GSE5296 and GSE47681), all based on the GPL1261 platform and contained 10 samples (four control and six SCI) and 12 samples (four control and eight SCI) were sequenced at 3 days post-injury (dpi) and 7 dpi, respectively ( 10 , 11 ). The GSE189070 dataset based on the GPL24247 platform containing single-cell RNA data from six mice in the uninjured group and 12 mice in the injured group were sequenced at 3 dpi and 7 dpi, which corresponds to the sequencing time of bulk RNA seq datasets ( 12 ). The study flow chart is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%